Wireless Participant Incentives Using Reloadable Bank Cards to Increase Clinical Trial Retention With Abused Women Drinkers: A Natural Experiment. Issue 13 (July 2019) - Rodgers, Melissa; Meisel, Zachary; Wiebe, Douglas; Crits-Christoph, Paul; Rhodes, Karin V.
Retaining participants in longitudinal studies is a unique methodological challenge in many areas of investigation, and specifically for researchers aiming to identify effective interventions for women experiencing intimate partner violence (IPV). Individuals in abusive relationships are often transient and have logistical, confidentiality, and safety concerns that limit future contact. A natural experiment occurred during a large randomized clinical trial enrolling women in abusive relationships who were also heavy drinkers, which allowed for the comparison of two incentive methods to promote longitudinal retention: cash payment versus reloadable wireless bank cards. In all, 600 patients were enrolled in the overall trial, which aimed to incentivize participants using a reloadable bank card system to promote the completion of 11 weekly interactive voice response system (IVRS) phone surveys and 3-, 6-, and 12-month follow-up phone or in person interviews. The first 145 participants were paid with cash as a result of logistical delays in setting up the bank card system. At 12 weeks, participants receiving the bank card incentive completed significantly more IVRS phone surveys, odds ratio (OR) = 2.4, 95% confidence interval (CI) = [0.01, 1.69]. There were no significant differences between the two groups related to satisfaction or safety and/or privacy. The bank card system delivered lower administrative burden for tracking payments for study staff. Based on these and other results, our large medical research university is implementing reloadable bank card as the preferred method of participant incentive payments.